Nutrient Loading Fosters Seagrass Productivity Under Ocean Acidification - Ravaglioli, Chiara (Sci Rep, 2017)
The effects of climate change are likely to be dependent on local settings. Nonetheless, the compounded effects of global and regional stressors remain poorly understood. Here, we used CO(2) vents to assess how the effects of ocean acidification on the seagrass, Posidonia oceanica, and the associated epiphytic community can be modified by enhanced nutrient loading. P. oceanica at ambient and low pH sites was exposed to three nutrient levels for 16 months. The response of P. oceanica to experimental conditions was assessed by combining analyses of gene expression, plant growth, photosynthetic pigments and epiphyte loading. At low pH, nutrient addition fostered plant growth and the synthesis of photosynthetic pigments. Overexpression of nitrogen transporter genes following nutrient additions at low pH suggests enhanced nutrient uptake by the plant. In addition, enhanced nutrient levels reduced the expression of selected antioxidant genes in plants exposed to low pH and increased epiphyte cover at both ambient and low pH. Our results show that the effects of ocean acidification on P. oceanica depend upon local nutrient concentration. More generally, our findings suggest that taking into account local environmental settings will be crucial to advance our understanding of the effects of global stressors on marine systems.